Participação dos receptores P2X7 presentes em células da glia do gânglio da raiz dorsal na nocicepção - Lemes, Júlia Borges Paes (2017)
In sensory ganglia, the cellular bodies of neurons are surrounded by glial cells called satellite cells. Recent studies point to a possible communication between neurons and satellite cells through the release of ATP and activation of P2X7 receptors present in glial cells. In addition, adjacent satellite cells may be connected through gap junctions. Still today, the communication between satellite cells and neurons has been implicated in chronic pain and in inflammatory processes. In this study we sought to evaluate the role of communication between neurons and satellite cells through the activation of the P2X7 receptors as well as of the communicating junctions in acute pain models. In primary cultures of dorsal root ganglia, we found that the administration of capsaicin leads to an increase of calcium in neurons and then in satellite cells. The response of satellite cells was blocked by A740003, a selective antagonist for P2X7 receptors, indicating that nociceptors when activated release ATP, which in turn activates P2X7 receptors in the glial cells. To assess the role of this in vivo cellular communication, the P2X7 antagonist or the gap junction blocker, carbenoxolone, were administered by intraganglionar injection (L5) and the effects of intraplantar injections of capsaicin, menthol or formalin in rats were evaluated. Both A740003 and carbenoxolone reduced nociception induced by capsaicin and menthol. In the formalin test, both substances affected only the second phase of the test, considered the inflammatory phase. Capsaicin selectively activates TRPV1 receptors while menthol activates TRPM8 receptors, and possibly TRPA1 receptors, which are expressed mainly in nociceptive neurons associated with C fibers. In addition, studies by other authors indicate that the first phase of the formalin test involves primarily the activation of Aδ fibers whereas the second phase involves the activation of Aδ and C fibers. Considering these data together with the present results, we can suggest that the communication between satellite cells and neurons also occurs in acute pain, but only, when it depends on the activation of C fibers. Thus, communication between neurons and satellite cells, via release of ATP and activation of P2X7 receptors, as well as communication between adjacent satellite cells through gap junctions seems to be involved in a rapid processing of the pain signal in the dorsal root ganglion.